Crystal and molecular structures of 4-substituted 3,4-dihydropyrimidin-2(1H)-ones studied by X-ray and AM1 and B3LYP calculations - Vega-Teijido, Mauricio; Zukerman-Schpector, Julio; Nunes, Fabio Macedo; Gatti, Paula M.; Stefani, Helio A.; Caracelli, Ignez [UNESP] (Oldenbourg Verlag, 2007)
(1) C13H13N3O5, Mr = 291.26, P (1) over bar, a = 7.4629(9), b = 7.9203(9), c = 12.126(2) angstrom, alpha = 86.804(5), beta = 78.471(7), gamma = 69.401(8)degrees, V = 657.3(2)angstrom(3), Z = 2, R-1 = 0.0454; (2) C11H12N2O4, Mr=236.23, Pbca, a=7.2713(9), b=14.234(1), c=20.848(3)angstrom, V= 2157.8(4) angstrom(3), Z=8, R-1=0.0504; (3) C13H13N2O3Cl, Mr = 280.70, P2/n, a = 17.344(2), b = 9.237(1), c = 18.398(2) angstrom; beta = 92.61(2)degrees, V = 2944.4(6) angstrom(3), Z = 8, R-1 = 0.0714. The conformational features of three 4-substituted-3-4-dihydropyrimidin-2(1H)-ones were investigated by computational and single crystal X-ray crystallographic studies. The geometries were optimized using semiempirical (AM1) and first principle calculations (B3LYP/6-31G**) methods, the rotational barriers for important functional groups were studied. In all structures the pyrimidinone rings are in a more or less distorted boat conformation. The phenyl and the furane rings are almost perpendicular to the best least-squares plane through the dihydropyrimidinone ring.
Keywords: calcium channel modulators; dihydropyrimidinones; single crystal structure analysis; X-ray diffraction; semiempirical AM1; first principle calculations